2022
DOI: 10.1016/j.ajic.2021.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the incidence of multidrug-resistant bacterial infections in an acute care hospital in Brazil

Abstract: Background The impact of COVID-19 on healthcare- associated infections (HCAI) caused by multidrug-resistant (MDR) bacteria that contribute to higher mortality is a growing area of study Methods This retrospective observational study compares the incidence density (ID) of HCAI caused by MDR bacteria (CRE, CRAB, CRP, MRSA and VRE) pre-COVID (2017-2019) and during the COVID-19 pandemic (2020) in overall hospitalized patients and in intensive care (ICU) units. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 34 publications
3
52
0
8
Order By: Relevance
“…But the prevalence of carbapenemresistant Klebsiella pneumoniae (CRKP) was not analysed in this study. 15 It was very interesting that in the ICUs of COVID-19 patients there was a lower prevalence of carbapenem-resistant Pseudomonas aeruginosa, MRSA, CREs (other than Klebsiella pneumoniae) and VRE. Reports from other cities in Brazil, for example São Paulo, showed an increase in VRE in some units.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But the prevalence of carbapenemresistant Klebsiella pneumoniae (CRKP) was not analysed in this study. 15 It was very interesting that in the ICUs of COVID-19 patients there was a lower prevalence of carbapenem-resistant Pseudomonas aeruginosa, MRSA, CREs (other than Klebsiella pneumoniae) and VRE. Reports from other cities in Brazil, for example São Paulo, showed an increase in VRE in some units.…”
Section: Discussionmentioning
confidence: 99%
“…Reports from other cities in Brazil, for example São Paulo, showed an increase in VRE in some units. 15 Another interesting aspect of the behavior of MDR bacteria during the SARS-Cov-2 pandemic was that, unlike what happened in the influenza A (H1N1) pandemic in 2009, where there was an increase in MRSA co-infections, 16,17 in the COVID-19 pandemic, there was an increase in the number of co-infections due to MDR Gram-negative bacteria and fungi. 18,19 Further studies are needed to understand whether it was the previous microbiological environment of the ICUs that amplified this dissemination of MDR bacteria or whether there are specific characteristics in the viral infections that predispose to colonization and infections by certain MDR bacterial groups.…”
Section: Discussionmentioning
confidence: 99%
“…Severe COVID-19 infection with respiratory failure requiring prolonged mechanical ventilation or use of extracorporeal membrane oxygenation is associated with an increased risk of secondary infections and emergence of MDR pathogens [ 101 •, 104 , 105 •]. Most studies addressing severely ill COVID-19 patients reported high rates of MDR pathogens [ 106 •, 107 ]. Furthermore, COVID-19 patient unit-level outbreaks due to MDR pathogens have been reported [ 108 – 110 ].…”
Section: Impact Of the Covid-19 Global Pandemic On Antimicrobial Resi...mentioning
confidence: 99%
“…In one retrospective single-center, case-control study, authors from Spain reported that COVID-19 patients had increased risk of nosocomial infections with carbapenemase-producing Enterobacteriaceae , with infections being severe, appearing in critically-ill patients, and associated with a high mortality. The aforementioned infection was the cause of death in about two thirds of the studied patients ( Pintado et al., 2022 ). In Brazil, the COVID-19 pandemic was correlated to an increase in incidence of carbapenem-resistant A. baumannii both in ICU and non-ICU settings ( Polly et al., 2021 ).…”
Section: Carbapenemase-producers Causing Co-infections In Covid-19 Pa...mentioning
confidence: 99%
“…The aforementioned infection was the cause of death in about two thirds of the studied patients ( Pintado et al., 2022 ). In Brazil, the COVID-19 pandemic was correlated to an increase in incidence of carbapenem-resistant A. baumannii both in ICU and non-ICU settings ( Polly et al., 2021 ). Likewise, the number of carbapenem-resistant Enterobacteriaceae isolated from COVID-19 patients in a Turkish hospital was higher than that isolated during an equal time period prior to the pandemic ( Karataş et al., 2021 ).…”
Section: Carbapenemase-producers Causing Co-infections In Covid-19 Pa...mentioning
confidence: 99%